Pengambilan Keputusan Etis Berdasarkan Gender, Tingkat Pendidikan, Pengalaman Kerja dan Religiusitas - Ivana Susilo; Yenni Sugiarti (Akutansi Bisnis & Manajemen ( ABM ), 2014)
This research examines the effect of gender, educational level, working experience and religiosity on ethical decision-making of accounting students. The main contribution is on the importance of ethical decition for accountants. Logistic regression is employed to analysis the effect and the sample of 128 undergraduate and professional accounting students are drawn. The results show that gender does not significantly affect ethical decision-making, while tingkat pendidikanand working experience do have significant effect on ethical decisions. Religiosity is not the most dominant ethical factor in decision makings if compared to other ethical factors.